ONTOLOGI SAINS PERSPEKTIF BARAT DAN ISLAM - Cahaya Cahaya; Dhiauddin Dhiauddin; Mukhairir Fikri Ihsan (Reflektika, 2022)
Ontology is a science that discusses the existing Nature which is the ultimate reality in the form of physical/concrete and spiritual/abstract.  In the western perspective, ontology gives rise to several schools, including: Materialism, Vitalism, Humanism and Existence.  Meanwhile, the ontology in the Islamic perspective gave rise to several schools, including: Paripatetic School, Suhrawardi Illumination School and Mulla Sadra Transcendent Theosophy.  The existence of several streams of Ontology, of course, this theory seeks to create new formulations that can provide answers to several problems according to the context.